2006
DOI: 10.1577/a05-003.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Six Feeding Regimens for Survival and Growth of Shortnose Sturgeon Fry

Abstract: The shortnose sturgeon Acipenser brevirostrum is a federally listed endangered fish species cultured for recovery efforts. Since high mortality and labor costs are associated with first-feeding sturgeon culture, particularly during the period of dietary conversion from live to formulated feed, we investigated the effects of six feeding regimens on the survival and growth of cultured shortnose sturgeon fry. During the 30d trial, five replicate groups (100 fish/replicate) of first-feeding shortnose sturgeon were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 12 publications
3
16
1
Order By: Relevance
“…This supports the findings of Ware et al (2006) that shortnose sturgeon Acipenser brevirostrum exhibited higher survival and growth in different types of co-feeding regimes compared with a live food diet. The results obtained with different co-feeding regimes suggest a different pattern of transition to FD in these two species of sturgeon.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This supports the findings of Ware et al (2006) that shortnose sturgeon Acipenser brevirostrum exhibited higher survival and growth in different types of co-feeding regimes compared with a live food diet. The results obtained with different co-feeding regimes suggest a different pattern of transition to FD in these two species of sturgeon.…”
Section: Discussionsupporting
confidence: 90%
“…However, the performance of MD's for a variety of fish species was considerably enhanced when co-fed with live zooplankton (Kanazawa, Teshima, Inamori, Sumida & Iwashita 1982;Szlaminska & Praybyl 1986;Ehrlich, Cantin & Rust 1989;Fermin & Bolivar 1991;Marte & Duray 1991;Tandler & Kolkovski 1991;Walford, Lim & Lam 1991;Person Le Ruyet et al 1993;Lavens, Sorgeloos, Dhert & Devresse 1995). Ware, Henne, Hickson and Charlesworth (2006) investigated the effects of six feeding regimes on the survival and growth of shortnose sturgeon Acipenser brevirostrum fry over 30 days using formulated diets and co-feeding. Mohler et al (2000) indicated high survival in Atlantic sturgeon Acipenser oxyrinchus oxyrinchus using Artemia nauplii and a commercial feed.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition plays a great role in fish growth and health (Bronzi et al 1999). Practices to provide only formulated feeds for sturgeons from the onset of exogenous feeding has led to drawbacks such as suboptimal survival and nearly complete mortality (Ware et al 2006;Mohler et al 2012;Ronyai and Feledi 2012). Thus, most of the sturgeons are cultured with live feed (e.g., Artemia or tubificids) as part of their first feeding regime.…”
mentioning
confidence: 99%
“…The resulting fry were then transitioned from a diet of live nauplii of brine shrimp Artemia spp. to a prepared starter fish diet according to methods developed by Ware et al (2006).…”
Section: Methodsmentioning
confidence: 99%